The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s12017-016-8401-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6

Abstract: Many population-based epidemiological studies have unveiled an inverse correlation between intake of herbal plants and incidence of stroke. C. nutans is a traditional herbal medicine widely used for snake bite, viral infection and cancer in Asian countries. However, its role in protecting stroke damage remains to be studied. Despite of growing evidence to support epigenetic regulation in the pathogenesis and recovery of stroke, a clear understanding of the underlying molecular mechanisms is still lacking. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Western blot analysis of proteins was performed as previously described [ 30 ], with mouse monoclonal antibody to Alox15 (1:500, Abcam, New Territories, HK) and antibodies to MAP-2, NeuN or α-tubulin (1:500, Santa Cruz, CA, USA). Protein bands were visualized by an enhanced chemiluminescence system (Merck Millipore, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis of proteins was performed as previously described [ 30 ], with mouse monoclonal antibody to Alox15 (1:500, Abcam, New Territories, HK) and antibodies to MAP-2, NeuN or α-tubulin (1:500, Santa Cruz, CA, USA). Protein bands were visualized by an enhanced chemiluminescence system (Merck Millipore, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies suggested that the neuroprotective effect of C. nutans was promising. From the studies by Tan et al [ 74 ] and Tsai et al [ 75 ], the 80% ethanol extract with a dose concentration less than 10 μ g/mL was able to suppress post-hypoxic histone deacetylase (HDAC) activation and hypoxic neuronal death in an oxygen-glucose deprivation- (OGD-) reoxygenation assay. It also decreased the levels of cytosolic phospholipase 2 (cPLA2) mRNA expression in mouse primary cortical neurons subjected to 0.5 h of OGD injury.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…For the past few decades, the research for C. nutans has been progressively done in a rapid trend. Broad-spectrum of pharmacological activities, which includes antioxidant [ 4 ], antiviral (herpes simplex virus (HSV), varicella-zoster virus, papillomavirus, and dengue virus) [ 5 ], anti-inflammatory [ 6 ], antibacterial [ 7 , 8 , 9 ], analgesic [ 10 , 11 , 12 ], antivenom [ 13 , 14 , 15 ], immunomodulating [ 16 , 17 ], neuroprotective [ 18 , 19 , 20 ], antidiabetic [ 21 , 22 , 23 ], α-glucosidase inhibitory [ 24 ], lipid-elevated inhibition [ 25 ], plasmid DNA protective [ 26 ], anti-angiogenic [ 27 ], anticancer [ 28 ], anti-proliferative [ 28 ], and antitumor as the latest biological action identified [ 29 ], has been very well reported in previous studies. Owing to significant economic benefits towards human health, the demand for this herb has been increased in recent years.…”
Section: Introductionmentioning
confidence: 99%